Feedlot fattening experiments with lambs. - Bell, T.D.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2012)
The tests this year compared whole milo with steam-rolled milo, and ground milo when fed with a standard roughage ration of ground sorghum fodder (little grain), plus a protein supplement and supplemental salt and limestone. The roughage comparisons included: (1) all sorghum fodder, (2) sorghum fodder and alfalfa hay, (3) sorghum silage and alfalfa hay, (4) sorghum silage and sorghum fodder, and (5) beet top silage and alfalfa hay. One lot of lambs received the standard ration of fodder, milo grain, and protein in pellets containing all three ingredients. The value of antibiotics was checked in one lot and the value of stilbestrol implants and progesterone-stilbestrol implants was checked in two other lots.
Keywords: Sheep; Feedlot; Stilbestrol implants; Progesterone-stilbestrol implants; Antibiotics